2020
DOI: 10.1002/jmv.26462
|View full text |Cite
|
Sign up to set email alerts
|

Cost‐effectiveness analysis of cytomegalovirus prophylaxis in allogeneic hematopoietic cell transplant recipients from a US payer perspective

Abstract: To evaluate the cost‐effectiveness of letermovir versus no prophylaxis for the prevention of cytomegalovirus infection and disease in adult cytomegalovirus‐seropositive allogeneic hematopoietic cell transplantation (allo‐HCT) recipients. A decision model for 100 patients was developed to estimate the probabilities of cytomegalovirus infection, cytomegalovirus disease, various other complications, and death in patients receiving letermovir versus no prophylaxis. The probabilities of clinical outcomes were based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 50 publications
(114 reference statements)
1
13
0
Order By: Relevance
“…On the other hand, several factors may have slowed down this policy such as the variable time interval between EMA approval and the authorization of letermovir prescription at different European countries, the costs of the drug prophylaxis and the need for every allogeneic-HCT unit to reformulate the annual budget and approve the costs for letermovir, and the attitude of the centres and haematologists to transfer quickly in the routine practice the indications coming from a clinical trial. Retrospective data from "real world" use and cost-effectiveness model analysis, confirmed that anti-CMV primary prophylaxis with letermovir is associated with a reduction of CMV infections, shorter hospitalizations, reduced costs and improvement of haematological and renal parameters [21][22][23]. In this regard, our interpretation of existing data support that a broader use of letermovir primary prophylaxis in the next future may result into an improvement of the overall transplant outcomes, as suggested by a post-hoc analysis on overall mortality conducted on the patients recruited in the phase III trial of letermovir versus placebo [24].…”
Section: Discussionmentioning
confidence: 85%
“…On the other hand, several factors may have slowed down this policy such as the variable time interval between EMA approval and the authorization of letermovir prescription at different European countries, the costs of the drug prophylaxis and the need for every allogeneic-HCT unit to reformulate the annual budget and approve the costs for letermovir, and the attitude of the centres and haematologists to transfer quickly in the routine practice the indications coming from a clinical trial. Retrospective data from "real world" use and cost-effectiveness model analysis, confirmed that anti-CMV primary prophylaxis with letermovir is associated with a reduction of CMV infections, shorter hospitalizations, reduced costs and improvement of haematological and renal parameters [21][22][23]. In this regard, our interpretation of existing data support that a broader use of letermovir primary prophylaxis in the next future may result into an improvement of the overall transplant outcomes, as suggested by a post-hoc analysis on overall mortality conducted on the patients recruited in the phase III trial of letermovir versus placebo [24].…”
Section: Discussionmentioning
confidence: 85%
“…By reducing the risk of CS-CMVi (thereby decreasing the use of pre-emptive therapy) and re-hospitalization, letermovir may help to reduce the healthcare resource use associated with allogeneic HSCT. A recent health economic model based on this phase III trial and local cost data showed that CMV prophylaxis with letermovir was considered a cost-effective option in adult CMV-seropositive recipients of an allogeneic HSCT from a US payer perspective [12]. These findings may be of particular relevance to US healthcare providers considering the timeframe associated with the bundled payment system used by most US commercial payers [13].…”
Section: Discussionmentioning
confidence: 90%
“…On the other hand, several factors may have slowed down this policy such as the variable time interval for the authorization of letermovir prescription at different European countries, the costs of the drug prophylaxis and the need for every allogeneic-HCT unit to reformulate the annual budget and approve the costs for letermovir, and the attitude of the centres and hematologists to utilise in the routine practice the indications coming from a clinical trial. Retrospective data from "real world" use and cost-effectiveness model analysis, con rmed that anti-CMV primary prophylaxis with letermovir is associated with a reduction of CMV infections, shorter hospitalizations, reduced costs and improvement of hematological and renal parameters [21][22][23] . In this regard, our interpretation of existing data support that a broader use of letermovir primary prophylaxis in the next future may result into an improvement of the overall transplant outcomes, as suggested by a post-hoc analysis on overall mortality conducted on the patient recruited in the phase III trial of letermovir versus placebo 24 .…”
Section: Discussionmentioning
confidence: 97%